Inverter-Based Circuit Design Techniques for Low Supply Voltages - Palani, Rakesh Kumar; Harjani, Ramesh; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book describes intuitive analog design approaches using digital inverters, providing filter architectures and circuit techniques enabling high performance analog circuit design. The authors provide process, supply voltage and temperature (PVT) variation-tolerant design techniques for inverter based circuits. They also discuss various analog design techniques for lower technology nodes and lower power supply, which can be used for designing high performance systems-on-chip.    .
1 Introduction -- 2 Biasing -- 3 Inverter based OTA Design -- 4 ADC Driver -- 5 Current Mirror Based Filter -- 6 All MOSCAP Based Continuously Tunable Filter -- 7 ADC.
Keywords: Electronic circuits; Electronics; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation